Synergistic Effect of Chlorpyrifos and Mancozeb on The Survival of Poecilia reticulata - Nugroho, Rully Adi; Wijaya, Andhika Ryan; Cahyaningrum, Desti Christian; Gestel, Cornelis Adrianus Maria Van (Biosaintifika: Journal of Biology & Biology Education, 2025)
Pesticides are essential in agricultural pest control, but may also harm non-target organisms. In Temanggung Regency, Indonesia, interviews with tobacco farmers revealed that the insecticide Dursban 200 EC (chlorpyrifos) and the fungicide Manzate 82 WP (mancozeb) are most commonly used, leading to the emission to the aquatic environment of both active ingredients, often resulting in mixtures. The present study aimed at determining the acute toxicity of chlorpyrifos, mancozeb, and their combination to guppy fish (Poecilia reticulata). A 96 h survival assay was conducted on male guppies exposed to the individual pesticides and their equitoxic mixtures. Mortality data were analyzed using a logistic dose-response model, and the toxicity of the mixtures was analyzed using the Concentration Addition (CA) and Independent Action (IA) models. Chlorpyrifos was slightly more toxic to P. reticulata than mancozeb, with LC50s of 1.81 and 3.45 mg a.i./L, respectively. The combination of chlorpyrifos and mancozeb resulted in enhanced toxicity due to synergistic interaction according to the CA model, which suggests different modes of action of the two active ingredients. When analyzed using the IA model, the interaction, however, was also synergistic. These findings highlight the need to assess both single and combined pesticide exposures in ecological risk evaluations and emphasize cautious use of pesticide mixtures to protect aquatic ecosystems.